1996
DOI: 10.1109/79.482137
|View full text |Cite
|
Sign up to set email alerts
|

Splitting the unit delay [FIR/all pass filters design]

Abstract: fractional delay filter is a device for bandlimited interpolation between samples. It finds applications in numerous fields of signal processing, including communications, array processing, speech processing, and music technology. In this article, we present a comprehensive review of FIR and allpass filter design techniques for bandlimited approximation of a fractional digital delay. Emphasis is on simple and efficient methods that are well suited for fast coefficient update or continuous control of the delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
437
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,058 publications
(467 citation statements)
references
References 86 publications
2
437
0
3
Order By: Relevance
“…We also found that these processes can be efficiently implemented by the Farrow-based variable digital filter (VDF) [15,16]. Important advantages of the proposed structure are that the VDF coefficients can be varied online cope with possibly changing timing jitters, and more importantly it can be implemented in hardware without any multiplications, apart from a limited number of multipliers required to implement the tuning variables [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also found that these processes can be efficiently implemented by the Farrow-based variable digital filter (VDF) [15,16]. Important advantages of the proposed structure are that the VDF coefficients can be varied online cope with possibly changing timing jitters, and more importantly it can be implemented in hardware without any multiplications, apart from a limited number of multipliers required to implement the tuning variables [17].…”
Section: Introductionmentioning
confidence: 94%
“…In the context of FDDF, it gives rise to a class of digital filters called VFDDFs, where the required samples at fractional sampling intervals can be computed by tuning a single parameter !, also known as tuning or spectral parameter [15,16,18,23,24]. The ideal response of the VFDDF is identical to (5), where in contrast to the case of fixed filter coefficients, the tuning parameter !…”
Section: Fractional Delay Digital Filtersmentioning
confidence: 99%
“…A 1-D translation with amplitude τ : s → s is achieved by means of a convolution with a fractional delay filter [10]:…”
Section: The H 2 O Algorithmmentioning
confidence: 99%
“…In this application, a TVFD element is conveniently approximated using Lagrange interpolation [4], which is often used in digital waveguide models due to its easy coefficient update, bounded magnitude response that does not risk the stability of the feedback loop, and a transient-free behavior in time-varying cases. The Farrow structure can be used to implement a Lagrange interpolation so that its transfer function is directly controlled by a single parameter d(n) [10], [11].…”
Section: Dual-delay-line String Modelmentioning
confidence: 99%